المساندة الاجتماعية وعلاقتها بالرضا عن الحياة لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم دراسة ميدانية بمصحة الحماديين ولاية المسيلة - جبلاحي شيماء; محدب ابتسام; اشراف: مناصرية عمر (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة الحالية إلى الكشف عن العلاقة بين المساندة الاجتماعية والرضا عن الحياة لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم، تكونت عينة الدراسة من (53) مريضا، من بينهم (18) ذكور و(35) إناث، تتراوح أعمارهم بين (20-81) سنة، وتم استخدام المنهج الوصفي التحليلي كونه يتلائم مع طبيعة الموضوع، ولتحقيق أهداف الدراسة تم استخدام مقياس المساندة الاجتماعية ومقياس الرضا عن الحياة، وبعد التحقق من ثبات وصدق الأدوات تم تطبيقها على عينة الدراسة، وقد تم التوصل إلى النتائج التالية: 1. توجد علاقة ارتباطية ذات دلالة إحصائية بين المساندة الاجتماعية والرضا عن الحياة لدى مرضى القصور الكلوي الخاضعين لعملية تصفية الدم. 2. لا توجد فروق ذات دلالة إحصائية في درجة المساندة الاجتماعية ودرجة الرضا عن الحياة لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم تبعاً لمتغير الجنس. 3. توجد فروق ذات دلالة إحصائية في درجة المساندة الاجتماعية لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم تبعا لمتغير السن. 4. لا توجد فروق ذات دلالة إحصائية في درجة الرضا عن الحياة لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم تبعاً لمتغير السن. 5. لا توجد فروق ذات دلالة إحصائية في درجة المساندة الاجتماعية ودرجة الرضا عن الحياة لدى مرضى القصور الكلوي المزمن الخاضعين لعملية تصفية الدم تبعاً لمتغير مدة المرض. الكلمات المفتاحية: المساندة الاجتماعية، الرضا عن الحياة، القصور الكلوي المزمن. ملخص الدراسة باللغة الإنجليزية : 1. The current study aimed to reveal the relationship between social support and life satisfaction in patients with chronic renal failure undergoing a blood filtering process. The study sample consisted of (53) patients, including (18) males and (35) females, aged between (20-81) years. The descriptive analytical method was used because it suits the nature of the subject. To achieve the objectives of the study, the social support scale and the life satisfaction scale were used. After verifying the stability and truth of the tools, they were applied to the study sample. The following results were reached: 1. There is a statistically significant correlation between social support and life satisfaction in renal failure patients undergoing blood filtration. 2. There are no statistically significant differences in social support and life satisfaction in patients with chronic renal failure undergoing blood filtration according to the gender variant. 3. There are statistically significant differences in social support in chronic renal failure patients undergoing a blood filtering process depending on the age variable. 4. There are no statistically significant differences in life satisfaction in patients with chronic renal failure undergoing blood filtration depending on the variable duration of the disease. 5. There are no statistically significant differences in social support and life satisfaction in patients with chronic renal failure undergoing blood filtration depending on the variable duration of the disease. Keywords: Social support, Life satisfaction, Chronic renal failure.